SISTEM INFORMASI PENGAGENDAAN SURAT KELUAR MASUK PADA SATUAN KERJA PERANGKAT DAERAH KECAMATAN POLANHARJO DENGAN APLIKASI MULTI USER - Henny Ekawati, Bebas Widada, Tri Irawati (STMIK Sinar Nusantara, 2015)
Polanharjo SKPD District of Klaten regency is one government agency at any time hold a routine, of course, is in desperate need of data have accurate level, the relevance of a reliable and also has a timeliness that in getting some information that is fit for use. The design of the system are made using Context Diagram, Hierarchy Process Input Output, Data Flow Diagram, Entity Relationship Diagram, Design Input, Output Design, Data Dictionary and Database Design. Results of the system archiving incoming and outgoing mail in the form of reports required by the relevant authorities so that can use overcome the problems of archiving incoming and outgoing mail. Keywords: Agenda, incoming mail, outgoing mail